2021
DOI: 10.7717/peerj.12267
|View full text |Cite
|
Sign up to set email alerts
|

Identification, expression, and functional analysis of Hsf and Hsp20 gene families in Brachypodium distachyon under heat stress

Abstract: Background The heat shock factor (Hsf) and small heat shock protein (sHsp, also called Hsp20) complex has been identified as a primary component in the protection of plant cells from ubiquitous stresses, particularly heat stress. Our study aimed to characterize and analyze the Hsf and Hsp genes in Brachypodium distachyon, an annual temperate grass and model plant in cereal and grass studies. Results We identified 24 Hsf and 18 Hsp20 genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The number of HSF family genes varies widely among plants. There are 17 HSF genes in Jatropha curcas (Zhang et al, 2020), 21 HSF genes in Arabidopsis (Nover et al, 2001), 23 HSF genes in Hordeum vulgare (Mishra et al, 2020), 24 HSF genes in brachypodium (Li, Jiang, et al, 2021a), 25 HSF genes in rice (Guo et al, 2008), 30 HSF genes in Phaseolus vulgaris (Zhang et al, 2022), 32 HSF genes in Coriandrum sativum (Pei et al, 2021), 64 HSF genes in Brassica napus (Zhu et al, 2017), and 78 HSF genes in Triticum aestivum (Zhou et al, 2019). In this study, a total of 25 HSF genes were identified in perennial ryegrass, and all HSF proteins had DBD, OD, and NLS conserved domains (Table 1).…”
Section: Relative Expressionmentioning
confidence: 99%
“…The number of HSF family genes varies widely among plants. There are 17 HSF genes in Jatropha curcas (Zhang et al, 2020), 21 HSF genes in Arabidopsis (Nover et al, 2001), 23 HSF genes in Hordeum vulgare (Mishra et al, 2020), 24 HSF genes in brachypodium (Li, Jiang, et al, 2021a), 25 HSF genes in rice (Guo et al, 2008), 30 HSF genes in Phaseolus vulgaris (Zhang et al, 2022), 32 HSF genes in Coriandrum sativum (Pei et al, 2021), 64 HSF genes in Brassica napus (Zhu et al, 2017), and 78 HSF genes in Triticum aestivum (Zhou et al, 2019). In this study, a total of 25 HSF genes were identified in perennial ryegrass, and all HSF proteins had DBD, OD, and NLS conserved domains (Table 1).…”
Section: Relative Expressionmentioning
confidence: 99%
“…The Food and Agriculture Organization Corporate Statistical Database (FAOSTAT) shows that cucumber is widely cultivated in the world and its cultivated area is next only to that of tomato and onion (FAOSTAT, 2022). HSP20 plays a crucial role in extreme temperatures (Peffer et al, 2019;Wu et al, 2019;Cui et al, 2021;Li et al, 2021;Sun et al, 2022;Zhou et al, 2022). Therefore, it is very necessary to study the roles of CsHSP20 genes under high temperature.…”
Section: Discussionmentioning
confidence: 99%